The Effective Strategies in Companies’ Performance Using the Partial Least Squares Approach - Mustafa, Saed Adnan (International Journal of Economics, Business and Management Studies, 2016)
Strategies have become important in companies in recent years to improve their companies performance this strategy has create a worthy interest on Public listed companies. Whereas previous research on the relationship between these strategies and company performance has largely been based on international data, this paper reviews the relationship between the adoption of the dimensions of corporate social responsibility, reputation and the companies’ performance of Malaysian public listed companies. 200 questionnaires were received from a population that had already worked in Malaysian public listed companies. Using the partial least squares equation modeling as the approach to examine the model. Furthermore, this paper found a significant relationship between CSR, reputation and company performance. The findings imply the need for public listed companies to improve their performance.